(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Beginning in 1947 Indo-Pak conflict has remained the oldest unresolved interstate conflict inthe world without any positive progress. There have been many interpretations of this persistent conflict,from realist and constructive viewpoints. Significantly, realist constructivism consolidates a few differentscientific aspects It takes a gander at how power structures influence examples of standardizing changein global relations and, on the other hand, how a specific arrangement of standards influences powerstructures. Both these aspects have been disregarded as factors that can make sense of why it will bechallenging to concoct enduring answers for the India-Pakistan struggle.